Resolution of a fourth ventricle epithelial cyst after ventriculoperitoneal shunting: case report - (:unkn) unknown (ELSEVIER SCIENCE INC, 2007)
Background: Symptomatic cysts of epithelial origin occurring in the fourth ventricle are very rare. When such a cyst is encountered, the treatment strategy includes surgical removal or fenestration of the cyst into subarachnoid space. Case 1: A 23-year-old male was diagnosed as having a cyst located in the fourth ventricle causing hydrocephalus; the patient underwent cyst removal via craniotomy. The histopathologic diagnosis was neuroepithelial cyst. Because clinical and neuroradiological findings persisted, he underwent VP shunting. The cyst disappeared and did not recur. Case 2: A 54-year-old woman was diagnosed as having a cystic mass in the fourth ventricle and dilatation of the ventricles. Magnetic resonance imaging showed the same findings as those of the first case. The patient refused craniotomy for total mass excision. Therefore, a VP shunt was applied. Postoperatively, the clinical findings and hydrocephalus improved, and complete disappearance of the cystic mass was observed unexpectedly. Both cases had 2 years of follow-up. Conclusion: There is no proven mechanism to explain resolution of fourth ventricle cysts after a supratentorial VP shunting. We hypothesize that disappearance of the cyst could result from rupture of its wall because of pressure gradient, which might be facilitated by a VP shunt. The current report should not be taken as an argument against cyst removal, which is the established way of treatment. However, considering that the pathogenesis and pathophysiology of these cysts are unclear, VP shunting should be considered especially for recurrent cases accompanied by hydrocephalus. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: cysts; central nervous system; ependymal; fourth ventricle; hydrocephalus; epithelium; neuroepithelial cell; magnetic resonance imaging; ventriculoperitoneal shunt; CENTRAL-NERVOUS-SYSTEM; NEUROEPITHELIAL CYSTS; 4TH VENTRICLE; POSTERIOR-FOSSA; ARACHNOID CYST; PATHOLOGICAL CORRELATION; ENTEROGENOUS CYSTS; NEURENTERIC CYST; MR; HYDROCEPHALUS